(untitled) (Bangladesh Journal of Otorhinolaryngology, 2022)
Background: Incidence of thyroid malignancy is increasing day by day in thyroid swelling. The exact cause of cancer is not known. But there are few predisposing factors in genesis of thyroid malignancy such as age, sex, geographical distribution, familial predisposition, radiation exposure, pre-existing thyroid disease. Papillary thyroid carcinoma is most common among all thyroid malignancy with high incidence of lymph node metastasis. The aim of this study is to find out the pattern of malignancy in thyroid swelling. Methods: This cross-sectional observational study was done in department of Otolaryngology- Head neck surgery; Dhaka Medical College Hospital for 6 months. 50 Patients with thyroid swelling undergone operative management were included. Results: Results of this study showed that the highest numbers of patients were in 31-40 years of age group numbering 20 (40%). There were 42 females comprising 84% and males comprising 8 (16%) with female to male ratio 5.25:1. Among the thyroid swelling 35 (70%) cases were solid & 15 (30%) cases were cystic and 38 cases were non-neoplastic and 12 cases were neoplastic. Among the 12 cases 7 cases were malignant. Papillary carcinoma was predominant having 6 (85.7%) cases and Follicular carcinoma was in 1 (14.28%) case and out of 7 cases metastatic cervical lymph node was in 1 (14.28%) case which was from papillary carcinoma. Conclusion: Incidence of thyroid malignancy in thyroid swellings is high. Male patients with thyroid swelling has more chance of thyroid malignancy and papillary thyroid carcinoma is the commonest of all thyroid malignancy with cervical neck node metastasis. Bangladesh J Otorhinolaryngol 2022; 28(1): 78-83